Alpha-fetoprotein (AFP) as tumor marker in a patient with urothelial cancer with exceptional response to anti-PD-1 therapy and an escape lesion mimic. Issue 1 (12th September 2018) - Melms, Johannes C.; Thummalapalli, Rohit; Shaw, Kristin; Ye, Huihui; Tsai, Leo; Bhatt, Rupal S.; Izar, Benjamin
Abstract : The development of a new lesion in a patient with a complete remission to anti-PD-1 therapy is highly concerning for a drug resistant escape lesion. Here, we present a case of a 62-year-old patient with chemotherapy-resistant metastatic urothelial cancer who had a complete remission to pembrolizumab. The patient's disease burden tracked closely to serum levels of alpha-fetoprotein (AFP) expressed by the tumor and served as an accurate tumor marker. Surveillance imaging revealed a solitary growing pulmonary nodule mimicking an escape lesion in the absence of an increase in AFP levels. Biopsy of this lesion revealed a benign intraparenchymal lymph node with no evidence of metastatic carcinoma. This case indicates that in some patients, biomarkers aberrantly expressed by their tumors, such as AFP in this patient, may be used as a tumor marker for response to anti-PD-1 therapy and emphasizes the importance of confirming potential escape lesions by pathologic examination.